Using VoA (Voice of America) to Improve Speaking Abilities of Autism Students in Learning English - Hamzah, Amir (Modality Journal: International Journal of Linguistics and Literature, 2024)
This research explained the English Language learning in the context of improving speaking abilities of autism students using VoA (Voice of America). Voice of America (VOA) is interactive media universal broadcaster possessed by the Joined together States government, which has broadcast different programs in 53 dialects since 1942 based in Washington, DC. This research focused in fourth grades of Banyuates Special School in 2023/2024 academic year who were taught using of media VoA Learning English in Website. This research is a quantitative research which also applied quasi experimental research which aims at finding out the effectiveness of using VoA as a Learning English website to improve the autistic student's speaking ability. This research involves two groups that were observed; they were experimental group and control group. The data were gathered for finding out the effectiveness of using VoA as a Learning English website to improve the autistic student's speaking ability. The finding showed that the use of VoA Learning English is effective through comparing the data between the experimental group and the control group in which it got < 0.05, which means H0 is rejected and H1 is accepted. It can be concluded that the VoA Learning English is effective as a medium in the teaching and learning process to improve students' speaking skills if the significant tailed results are < 0.05 Abstrak Penelitian ini menjelaskan tentang pembelajaran Bahasa Inggris untuk meningkatkan   kemampuan berbicara siswa autis dengan menggunakan VoA (Voice of America) Voice of America (VOA) dapat diartikan sebagai media penyiaran interaktif yang dimiliki oleh pemerintah Amerika Serikat yang telah menyiarkan berbagai program dalam 53 dialek sejak tahun 1942 yang berpusat di Washington DC. Penelitian ini difokuskan pada siswa kelas IV Sekolah Luar Biasa (SLB) Negeri Banyuates tahun ajaran 2023/2024 yang diajar dengan menggunakan media pembelajaran bahasa Inggris berbasis website. Penelitian ini merupakan penelitian kuantitatif dengan metode quasi eksperimen yang bertujuan untuk mengetahui efektivitas penggunaan media VoA dalam website pembelajaran bahasa Inggris untuk meningkatkan kemampuan berbicara siswa autis. Penelitian ini melibatkan dua kelompok yang diamati dalam desain penelitian ini yakni kelompok eksperimen dan kelompok control. Penelitiian ini bertujuan untuk mengumpulkan data terkait dengan efektivitas penggunaan VoA sebagai situs web pembelajaran bahasa Inggris untuk meningkatkan kemampuan berbicara siswa autis. Hasil penelitian menunjukkan bahwa penggunaan VoA efektif yang diketahui dengan cara membandingkan hasil nilai antara kelompok eksperimen dan kelompok kontrol dan mendapatkan hasil < 0,05 yang berarti H0 ditolak dan H1 diterima. Dapat disimpulkan bahwa VoA Learning English efektif sebagai media dalam proses belajar mengajar untuk meningkatkan kemampuan berbicara siswa jika hasil signifikan tailed < 0.05.   Kata Kunci : Pembelajaran Bahasa Inggris, siswa autis, VoA (Voice of America)